Self-efficacy in increasing physical activity of coronary heart disease patients: a cross-sectional study - Muliantino, Mulyanti Roberto; Qadri, Nindy Zumratul; Afriyanti, Esi; Sarfika , Rika (Universitas Airlangga, 2024)
Introduction: This study aimed to determine the association of physical activity and self-efficacy in patients with coronary heart disease. Methods: A cross-sectional study was conducted among outpatients of coronary heart disease at a cardiovascular center. A total of 238 coronary heart disease patients were included in the study using a purposive sampling technique. The self-efficacy was measured using the cardiac self-efficacy scales (CSE), and the physical activity was measured using the long form International Physical Activity Questionnaire (IPAQ). Data analysis used the Chi-square test, Spearman correlation test and multivariate linear regression. Results: Self-efficacy was strongly positively correlated with physical activity in coronary heart disease patients (r = 0.956; p = 0.001). Domain-specific correlations included domestic (r=0.419, p<0.001), work (r=0.383, p<0.001), leisure time (r=0.296, p<0.001), and transport (r=0.247, p<0.001). Multiple linear regression analysis showed that employment status had the most significant negative impact on physical activity (B = -246.477), while age (B = 123. 889) and self-efficacy (B = 93.513) were positively associated with physical activity. These results indicate that higher self-efficacy and older age are linked to increased physical activity, whereas employment status is associated with decreased physical activity. Conclusions: In this population, self-efficacy, remaining working status and age are important factors of physical activity in coronary heart disease patients. Keywords: coronary heart disease, good health and well-being, physical activity, self-efficacy